2003
DOI: 10.1111/j.1469-8137.2004.00974.x
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of C4photosynthesis

Abstract: Contents Summary 341 Introduction 342 What is C4 photosynthesis? 343 Why did C4 photosynthesis evolve? 347 Evolutionary lineages of C4 photosynthesis 348 Where did C4 photosynthesis evolve? 350 How did C4 photosynthesis evolve? 352 Molecular evolution of C4 photosynthesis 361 When did C4 photosynthesis evolve 362 The rise of C4 photosynthesis in relation to climate and CO2 363 Final thoughts: the future evolution of C4 photosynthesis 365 Acknowledgements 365 References 365 Summary C4 photosynthesis is a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
1,122
3
36

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,202 publications
(1,185 citation statements)
references
References 203 publications
(391 reference statements)
24
1,122
3
36
Order By: Relevance
“…Studies on parallel vascular bundles in grasses showed that C4-type species present smaller distance between the vascular bundles than C3 type (Ueno et al, 2006). Such characteristic, present in C4-type plants, conveys higher ability in photosynthate translocation and higher water distribution in environments with water restriction and high temperatures (Sage, 2004). Just as a greater phloem thickness could increase the photosynthetic flow, a reduced space between the vascular bundles in the selection cycles of 'Saracura' maize could also increase this flow, because it would promote higher photosynthate distribution (Roth-Nebelsick et al, 2001) in addition to a higher water distribution.…”
Section: Resultsmentioning
confidence: 97%
“…Studies on parallel vascular bundles in grasses showed that C4-type species present smaller distance between the vascular bundles than C3 type (Ueno et al, 2006). Such characteristic, present in C4-type plants, conveys higher ability in photosynthate translocation and higher water distribution in environments with water restriction and high temperatures (Sage, 2004). Just as a greater phloem thickness could increase the photosynthetic flow, a reduced space between the vascular bundles in the selection cycles of 'Saracura' maize could also increase this flow, because it would promote higher photosynthate distribution (Roth-Nebelsick et al, 2001) in addition to a higher water distribution.…”
Section: Resultsmentioning
confidence: 97%
“…In the majority of C3 plants, oxygen reduces CO 2 fixation by some 25% (see e.g. Lambers et al, 1998 andSage 2003, for a full discussion).…”
Section: The Importance Of Oxygenic Photosynthesis For the Evolution mentioning
confidence: 99%
“…Many studies addressing climatic effects on C 4 grass distribution (Teeri and Stowe 1976;Chazdon 1978;Vogel and Fuls 1978;Rundel 1980;Hattersley 1983;Collins and Jones 1985;Klink and Joly 1989;Paruelo and Lauenroth 1996;P'yankov et al 2000) reported the positive correlation between growing season temperature and C 4 grass abundance. Whereas precipitation gradients seemed to have less impact on C 3 and C 4 grass distribution globally (Sage 2004).…”
mentioning
confidence: 99%
“…In C 3 photosynthesis, CO 2 is directly fixed by the oxygen sensitive ribulose-bis-phosphate carboxylase/oxygenase (Rubisco) and the first stable fixation product is the C 3 compound phosphoglyceric acid (PGA). In C 4 photosynthesis, CO 2 is initially fixed by the oxygeninsensitive phosphoenolpyruvate carboxylase (PEPC) and the first stable fixation product is the C 4 compound, malic acid (Sage 2004). C 4 photosynthesis is a major evolutionary success and about of the species in the grass family utilize this pathway.…”
mentioning
confidence: 99%
See 1 more Smart Citation